Cryptocurrency and the Future of the World Currency - Aang Kunaifi; Muhamad Wildan Fawa'id; Ani Faujiah (Islamic Research, 2022)
Cryptocurrencies and blockchain technology are increasingly loved, especially the COVID-19 pandemic sweeping the world. Some people choose to trade, invest, or mine using cryptocurrency because it is considered practical and able to generate fantastic profits. This article was written to analyze the prospects and implications of using cryptocurrency as a currency. To explore and describe the prospects and implications of cryptocurrency as a currency, a study was conducted with a literature review approach from secondary sources regarding the reasons for the prohibition of cryptocurrencies, the instability of crypto values, and without a clear underlaying of assets. Furthermore, the study in this article is expected to be able to explain the advantages and disadvantages of cryptocurrencies as well as alternative efforts in creating a stable and fair world currency